Implementasi Manajemen Pendidikan Islam di Sekolah Dasar Muhammadiyah Program Khusus Nogosari Boyolali Jawa Tengah Tahun 2013 - Aziz, Abdul; , Prof. Dr. Bambang Sumardjoko, M.Pd; , Dr. Abdulah Aly M.Ag (2014)
The development of islamic education school can't be conduct by partial, but need more all intellectual developing as consequent from general school with Islamic characters. Total Islamic education at Special Program Muhammadiyah Elementary School in Surakarta district, make it be barometer is Kotabarat Special Program Muhammadiyah Elementary School. The aims of the research are: to describe about planning, organizing, implementing, controlling, and evaluation islamic education institution in education management. This research is a qualitative with ethnographic research design. Implementation of the research done in Nogosari Muhammadiyah Special Program Elementary School. The collecting data, used observation, interview, and documentation. Informants of this study was head madrasas, deputy head of the curriculum, the deputy head of the public relations, classroom teacher, head of the madrasa committee, one of the guardians of the students, and one student. Analysis data conduct by reduse, display, and verification to conclusion. The study concluded: 1) Islamic educational institutions planning to have a character who refers to the the Islamic Aqeedah, involving BPH (Daily Board) and Supervisor of Education Department through UPTD, 2) Organizing Islamic educational institutions in coordination educators in accordance with the educational background of teachers, and accordance with job descriptions, 3) Implementation of Islamic educational institutions capable of forming a Muslim man Ulul Albab quality and character of Islamic, equipped with learning facilities, implementation of learning to apply the full day school concept, implement Shari'ah-Integrated curriculum to oriented on integrated of qouliyah and kauniyah knowledge, 4) Education activities observed and supervised by the UPTD department and and Dikdasmen of Muhammadiyah district Boyolali, 5) Evaluation of Islamic educational institutions by conduct a self-evaluation, and then had discussions together, evaluation activities are open to suggestions and criticisms from the public, evaluation conducted jointly by both principals, teachers or school administrators.